2014
DOI: 10.1063/1.4861205
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Griffith's phase in La0.4Bi0.6Mn1−xTixO3 perovskite oxide

Abstract: amples of La0.4Bi0.6Mn1−xTixO3 have been prepared and their microstructure, composition, and magnetic properties have been investigated for x = 0.05, 0.1, and 0.5.The deviation in the inverse susceptibility behavior from Curie-Weiss law and increase in susceptibility exponent indicates the evolution of the Griffith's phase in La0.4Bi0.6Mn1−xTixO3 around TC. The presence of Griffith's Phase is inferred due to magnetic frustration with increasing Ti concentration. The deviation between field cooled and zero fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 12 publications
2
11
1
Order By: Relevance
“…This nature of absence of long range FM interactions around magnetic TC likely leads to a phenomenon called Griffith's phase [4,10]. This is shown by the evidence of the downturn deviation from the characteristic Curie-Weiss linear law and the formation of FM clusters embedded in host PM matrix which is already been reported by us for the aforesaid and similar kind of sample [4,10].…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…This nature of absence of long range FM interactions around magnetic TC likely leads to a phenomenon called Griffith's phase [4,10]. This is shown by the evidence of the downturn deviation from the characteristic Curie-Weiss linear law and the formation of FM clusters embedded in host PM matrix which is already been reported by us for the aforesaid and similar kind of sample [4,10].…”
Section: Resultsmentioning
confidence: 62%
“…This is shown by the evidence of the downturn deviation from the characteristic Curie-Weiss linear law and the formation of FM clusters embedded in host PM matrix which is already been reported by us for the aforesaid and similar kind of sample [4,10].…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Recently it has been shown that though Ti 4+ prefers to occupy Mn 4+ sites, at high doping levels it also randomly distributed at Mn 3+ sites leading to oxygen non stoichiometry (cation deficiency) or in-homogeneities [10,11]. Thus substitution of Ti should produce strain on Mn 3+ −O−Mn 4+ network by the formation of Mn 3+ −O−Ti 4+ chains.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies we have reported spin glass (SG)/cluster glass (CG) and Griffith's phase behavior at very low and intermediate temperatures in La .ସ Bi . Mn ଵି୶ Ti ୶ O ଷ with x=0.05 and 0.1samples respectively [10,11]. Now in present work we focus on the critical behavior near the magnetic phase transition and their analysis using various techniques such as modified Arrott plot (MAP), Kouvel-Fisher (KF) method, scaling-equation-of-state analysis and the critical magnetization isotherm.…”
Section: Introductionmentioning
confidence: 99%